PENGARUH GCG, LEVERAGE, FIRM SIZE TERHADAP EARNINGS MANAGEMENT INDUSTRI DASAR, BARANG, KONSUMSI - Sidharta, Alyssa Christina; Bangun, Nurnainun (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study is to obtain empirical evidence regarding the effect of good corporate governance, leverage, and firm size on earnings management in companies in the basic and chemical industry sector, various industrial sectors, and the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX). period 2019-2021. This study used 62 samples and 186 data from companies in the basic and chemical industry sector, various industrial sectors, and the consumer goods industry sector selected by purposive sampling method. The data in this study were inputted and calculated using the Microsoft Excel program and processed using the Eviews 12 program. The results of this study indicate that good corporate governance on institutional ownership and leverage variables have no effect on earnings management. Meanwhile, firm size has a positive and significant influence on earnings management.